(untitled) (Journal of Economic Research & Business Administration, 2018)
The selected theme of the research is currently one of the most actual theme, because more and more actively the processes of digitalization are introduced into different spheres of society, forming separate elements of the digital economy. The authors consider the formation of the “SMART” model of the university, which is based on the best European practices using methods of scientific knowledge. In order to implement the state program «Digital economy of the Russian Federation», an increasing number of institutions are improving information technology, their infrastructure support is included in the network interaction, in this connection, it is necessary to create an environment in universities that allows you to establish communication and build analytical reports not only within the university and best practices with the best representatives of business. The authors propose a model of building a «SMART» university, which will facilitate systematic interaction with stakeholders and ultimately contribute to improving the quality of educational institutions. Thus, it is the solution of specific global and local problems that will contribute to the involvement of society in the sphere of higher education and university science, and, as a consequence, involvement in the SMART model of the university.